Effects of Stimulation Rate With the FS4 and HDCIS Coding Strategies in Cochlear Implant Recipients. Issue 7 (August 2016) - Riss, Dominik; Hamzavi, Jafar-Sasan; Blineder, Michaela; Flak, Stefan; Baumgartner, Wolf-Dieter; Kaider, Alexandra; Arnoldner, Christoph
Abstract : Objective: The aim of the present study was to evaluate the effect of stimulation rate on speech perception and sound quality for the fine structure strategy FS4 and the envelope-based strategy high definition continuous interleaved sampling (HDCIS). Study Design: Randomized crossover trial with four conditions. Setting: Tertiary referral. Patients: Twenty-six postlingually deafened adult cochlear implant (CI) recipients were included. Intervention: All subjects were equipped with four coding strategies: FS4 with high rate on the envelope channels (on average 1376 pps/ch), FS4 low rate (750 pps/ch), and HDCIS with the same high and low rates. A "flat-charge map" was used for all four strategies. Only the loudness was balanced between programs. All tests were performed acutely in a double blind manner and a randomized sequence. Main Outcome Measures: Monosyllables in quiet and subjective sound quality. Results: Mean monosyllables scores at 65 dB in quiet were 25.5% correct with HDCIS low rate, 27.2% correct with HDCIS high rate, 25.2% with FS4 low rate, and 33.1% with FS4 high rate. Performance with high stimulation rates was significantly higher than with the low rate settings. Subjective sound quality measured with visual analogue scales showed that for naturalness of speech, the improvement with a high rate version was only evident with the FS4 strategy. In both FS4 and HDCIS, higher stimulation rates elicited a higher pitch and were perceived as less dull than lower rates. Conclusion: A high rate of stimulation resulted in better speech recognition in both strategies and a favorable subjective sound quality for FS4 in all tested settings.